مساهمه في دراسة بعض أنواع الهدبيات الطفيلية(حيوانات أوالي) عند أسماك الكارب العادي (Cyprinus carpio L.) في مزرعة السن (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
أجريت الدراسة على 420 سمكة كارب عادي بأعمار من 40 يوم حتى سنتين, أخذت العينات عشوائيا بفاصل زمني لا يقل عن 15 يوم من مزرعة السن خلال الفترة 10/2000-10/2001. تم عزل وتصنيف 3 أنواع طفيلية من الحيوانات الأوالي الهدبية هي Trichodina intermedia, Chilodonella cyprini and Ichthophthirus multifiliis, تواجدت على الجلد والزعانف عموما. اختلفت هذه الأنواع في نسب خمجها (إصابتها) للأسماك حيث بلغت على التوالي %43,57 ;%3,81 ;%11,43, وقد أبدت معظم هذه الطفيليات الهدبية علاقة مباشرة ببعض المؤشرات البيئية خصوصا الحرارة. صنفت هذه الأنواع الطفيلية لأول مرة في مياه الساحل السوري. A total of 420 carp fish (Cyprinus carpio L.) aged between 40 days to more than two years old were examined during the period lasting from October 2000 till October 2001,samples were collected randomly nearly every fortnight, from Al-Sin fish farm. Isolation and classification were performed for three parasitic  species of ciliatic Protozoa which were Trichodina intermedia and Chilodonella cyprini as well as Ichthyophthirus multifiliis deposited on the tegument and fins particulary. These species varied in the rates of  their fish- infection ,which were 43.57%, 3.81%, 11.43%. . Most of these ciliatic parasites have shown direct relationship with some environmental factors particulary temperature. These parasitic species were recorded for the first time at the Syrian coast fresh water resorces.